COVID-19 - Laboratory Diagnosis for Clinicians - Vieira, Luisane Maria Falci (2020)
COVID-19 (coronavirus disease 2019) is an infectious disease caused by the new coronavirus associated with severe acute respiratory syndrome 2 (SARS-CoV-2). Coronaviridae comprises a large family and at least seven members are known to cause respiratory diseases in humans. Coronaviruses have the ability to infect virtually all major groups of animals and, eventually, can infect humans. SARS-CoV-2 is the third coronavirus to cross the species barrier and infect humans. This virus was identified in an outbreak of pneumonia in the city of Wuhan, Hubei province, China, in December 2019. Its entire genome is inscribed on a single ribbon of ribonucleic acid. Some proteins present on the surface of the virus act as facilitators of its entry into host cells, others, apparently, are related to its pathogenesis. Coronaviruses are responsible for respiratory infections in humans and some animals. The infection is often mild to moderate in intensity, but some coronaviruses can cause serious illnesses, such as Severe Acute Respiratory Syndrome (SARS) (SARS), which occurred in 2002 and the Middle East respiratory syndrome. (MERS, from Middle East respiratory syndrome). Coronaviruses can activate an excessive and unregulated immune response, which can promote SRAG development. Although the lung is one of the target organs, the hypoxia mechanism is systemic and other organs suffer both the lack of oxygen and the disruption of inflammation control mechanisms.